2012
DOI: 10.1111/j.1750-3841.2012.02940.x
|View full text |Cite
|
Sign up to set email alerts
|

Porosity and Water Activity Effects on Stability of Crystalline β‐Carotene in Freeze‐Dried Solids

Abstract: β-Carotene expresses various nutritional benefits; however, it is sensitive to oxygen and the degradation contributes to loss of nutritional values as well as product color. To increase stability of β-carotene in freeze-dried foods, the amount of oxygen penetration need to be limited. The modification of freeze-dried food structures, for example, porosity and structural collapse, components, and humidity effectively enhance the stability of dispersed β-carotene in freeze-dried solids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…After storage (91 days, 35 °C, air), 87.5% ± 1.3% of the carotenoids were degraded in FD powders while only 44.9% ± 0.8% were degraded in the SD-Ref. Other authors have shown that the microstructure and inner porosity of FD particles, influences the diffusion of oxygen through the dried particle and thus the oxidation of an encapsulated component [23]. The fast oxidation of carotenoids in the FD matrix compared to the SD powder is likely to be caused by increased mobility of external oxygen in the porous FD particle [24].…”
Section: Resultsmentioning
confidence: 99%
“…After storage (91 days, 35 °C, air), 87.5% ± 1.3% of the carotenoids were degraded in FD powders while only 44.9% ± 0.8% were degraded in the SD-Ref. Other authors have shown that the microstructure and inner porosity of FD particles, influences the diffusion of oxygen through the dried particle and thus the oxidation of an encapsulated component [23]. The fast oxidation of carotenoids in the FD matrix compared to the SD powder is likely to be caused by increased mobility of external oxygen in the porous FD particle [24].…”
Section: Resultsmentioning
confidence: 99%
“…This was explained by the sugars' ability to exert higher fluidity due to the increased T-T g (Harnkarnsujarit et al, 2012a;Harnkarnsujarit et al, 2012b), resulting in a partial flow and protective coating, reducing porosity and oxygen diffusion.…”
Section: Wall Materials For Freeze Drying Encapsulation and Additivesmentioning
confidence: 97%
“…Structural collapse occurring during freeze drying might also lead to enhanced carotenoid retention during storage (Harnkarnsujarit et al, 2012a). Investigating the storage stability of β-carotene entrapped in freeze dried maltodextrin systems revealed that the structural collapse upon freeze drying at temperatures below Tg´ and Tm´ was associated with improved β-carotene retention.…”
Section: General Aspectsmentioning
confidence: 97%
See 2 more Smart Citations